The Exploratory Study of Business and STEM Students’ Perceptions of LinkedIn - Zhang, Xia; Chen, Lin; Fu, Yujian (Journal of Accounting, Business and Management (JABM), 2025)
Our study examines whether there are differences mainly between business students and science, technology, engineering, and math (STEM) students’ perceptions of LinkedIn when they use LinkedIn to construct their professional and social identity, as a social capital, as a platform for building relationship with trust, as a platform of professional or business opportunities, and as an interactive learning resource. Our study employs a survey among college students at two different settings of public and private universities in the U.S. The findings reveal that there are no significant differences in business students or STEM students’ perceptions of LinkedIn as a social capital, or as a platform of building relationship with trust, or as a platform of professional career development. However, our findings reveal that business and STEM students have different perceptions and usage of LinkedIn as a resource for interactive learning. Our study benefits college students to utilize LinkedIn effectively in their learning and career. Our study fills the gap to examine the differences between young business students and STEM students’ perceptions of LinkedIn at two higher educational institutions.